Crystallization Kinetics Of Coconut Oil Based On Gompertz Model - Mursalin, Mursalin (Indonesian Food Science and Technology Journal, 2017)
The cooling rate and temperature of crystallization has been proven to be very influential on the rate of crystal formation oil. Oil crystallization kinetics can be measured by monitoring changes in the solid fat content(SFC) of oil during cooling process. In this study, SFC measuredusing pulsed Nuclear Magnetic Resonance (pNMR). Four levels of cooling rates and temperature crystallization studied. Crystallization kinetics parameters were measured by applying the model of Gompertz. Gompertz model used to explain the induction time, the increase in the maximum rate of crystallization and the crystalline polymorphic. Crystallization was done by heating the oil at a temperature of 70°C for 10 minutes prior to rapid cooling to 29°C. Then, rate of cooling from 29°C to the crystallization temperature (critical cooling rate) was set below 2°C/minutes. During the process, the oil was stirred at 15 rpm. Solid fraction was measured periodically since the crystallization temperature was reached until maximum solid fraction was achieved. The results showed that the Gompertzmodel able to quantitatively describe the crystallization kinetics of coconut oil. Lower critical cooling rate reduces the induction time of crystallization but accelerate the maximum increase rate of crystallization. Crystallization temperature has a negative correlation with the induction time and the maximum increase rate of crystallization. In the crystallization of coconut oil, critical cooling rate and crystallization temperature are only influence on the thermodynamics and kinetics of crystallization but not on its polymorphic formation.